Implementasi Critical Path Method Dalam Alur Proses E-Tendering Pengadaan Barang/Jasa - Chairani, Nanda; Rozi, Syamsyida (Politeknik Negeri FakFak, 2025)
Procurement of goods/services is an activity to obtain goods/services whose process starts from planning needs and then the e-tendering process is carried out. In optimizing the e-tendering process flow for procurement of goods/services, a method called the critical path or critical path method (CPM) can be used. Critical path method (CPM) is a technique used to determine the most important (most critical) series of activities and the total duration in a project or job. Based on the analysis that has been carried out, the optimal time for the e-tendering process flow for procurement of goods/services is 27 days with a critical path path of A-B-C-E-F-G-H-I-J-K-L-M-N-O-P. Activities that are on the critical path include auction registration (A), response of interest and disinterest (B), downloading documents (C), input of bids (E), opening of bids (F), administrative evaluation (G), qualification evaluation (H), technical evaluation (I), price evaluation (J), proof of qualifications (K), negotiation (L), determination of the winner (M), announcement of the winner (N), objection period (O), and letter of appointment of goods/services provider (P).